The Political Participation of Portuguese Young Adults on Social Media: A Civic Voluntarism and Reasoned Action Approach - Santos, Marta Almeida dos (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science